La medusa, el mono y la marioneta : Teología política y erótica en el peronismo - Intersimone, Luis Alfredo (Book collections on Project MUSE., 2022)
"The medusa, the monkey and the puppet studies the discursive genealogy of Peronism through the meticulous reading of texts by Eva Perón, Borges, Cortázar, Walsh, Erminda Duarte, Pedro Ara, Copi and T.E. Martinez. By unifying three theoretical components - the political, the sacred, and the erotic - based on Carl Schmitt's political theology, Freud's metapsychology, and Rene Girard's ideas about violence and the sacred, the book exposes the contingent articulations of Peronism in controversy with its political adversary, Liberalism. The analysis introduces several original concepts, such as political teratology, 'imputrefiction' and prosthetic sovereignty, which illuminate long-standing discussions about national culture, the necrophilic tendency, or the obsession with Evita's embalmed body by revealing condensation libidinal of political identity in the sovereign body or corpse, site of sacrifice, pain and fetishism"--